Identifying the Factors Impacting Bridge Deterioration in the GCC - Al-Rashed, Rawan Abdullah (2023)
A Master of Science thesis in Civil Engineering by Rawan Abdullah Al-Rashed entitled, “Identifying the Factors Impacting Bridge Deterioration in the GCC”, submitted in April 2023. Thesis advisor is Dr. Akmal Abdelfatah and thesis co-advisor is Dr. Sherif Yehia. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).